2014
DOI: 10.1111/jsbm.12106
|View full text |Cite
|
Sign up to set email alerts
|

Trade Credit, Bank Credit, and Flight to Quality: Evidence from French SMEs

Abstract: This paper investigates the impact of the global financial crisis on the allocation of credit to small and medium-sized enterprises (SMEs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(96 citation statements)
references
References 100 publications
(198 reference statements)
11
85
0
Order By: Relevance
“…In the South, SMEs more often tend to be in the trade-financed SME cluster (17.5%). This result can be explained by the generally longer payment periods in these countries (EPI 2014;Garcia-Teruel and Martinez-Solano 2010;Marotta 2005;Psillaki and Eleftheriou 2014). The finding that 22.6% of SMEs in Northern Europe are trade-financed SMEs is in line with the results of Demirgüç-Kunt and Maksimovic (2001).…”
Section: Country-specific Characteristicssupporting
confidence: 80%
See 1 more Smart Citation
“…In the South, SMEs more often tend to be in the trade-financed SME cluster (17.5%). This result can be explained by the generally longer payment periods in these countries (EPI 2014;Garcia-Teruel and Martinez-Solano 2010;Marotta 2005;Psillaki and Eleftheriou 2014). The finding that 22.6% of SMEs in Northern Europe are trade-financed SMEs is in line with the results of Demirgüç-Kunt and Maksimovic (2001).…”
Section: Country-specific Characteristicssupporting
confidence: 80%
“…However, most studies in the past only differentiated between external equity and external debt, and did not take into account that a variety of external financing instruments exist, which can complement and/or substitute traditional debt or equity instruments (Beck et al 2008;Berger and Udell 1998;Casey and O'Toole 2014;Cosh et al 2009). Furthermore, it has been found that these effects change over the business cycle and in particular in times of financial crises (Casey and O'Toole 2014;Psillaki and Eleftheriou 2014). Table 1provides an overview of relevant empirical studies.…”
Section: Introductionmentioning
confidence: 99%
“…This is attributed to the fact that, the larger the firm's size, the better the APP performance [28] . A study conducted by [21], shows that small companies heavily depend on trade credit leading to an increase in APP.…”
Section: Accounts Payable Periodmentioning
confidence: 99%
“…The flight-to-quality phenomenon has been attracting considerable scientific interest (Jones 2012;Briere, Chapelle, and Szafarz 2012;Rösch and Kaserer 2013;Pagano and Strother 2013;Psillaki and Eleftheriou 2014;Chabot 2014;Guerrieri and Shimer 2014). In spite of the continuous reappearance of flight-to-quality events along the economic history, the first mention related to these phenomena was made only less than two decades ago by Bernanke, Gertler, and Gilchrist (1996).…”
Section: Introductionmentioning
confidence: 99%